(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
Relationships within the family Phytolaccaceae sensu lato were examined based on internal transcribed spacer (ITS) sequences of nuclear ribosomal DNA (nrDNA). The study revealed Phytolacca L. as taxonomically the most difficult genus in the family with completely unknown phylogeny. Molecular evidence was used from nrDNA ITS sequences of about 90% of the species for maximum parsimony analyses, and the molecular phylogenetic analyses defined a monophyletic Phytolacca. This first molecular phylogenetic study of Phytolacca concludes that the relationships among the species within the genus do not show harmony with the generic classification based on morphology. These results set the stage for a more detailed phylogenetic analysis of Phytolacca. Bangladesh J. Plant Taxon. 22(1): 18, 2015 (June)